A BIBLIOMETRIC ANALYSIS ON ISLAMIC BUSINESS EDUCATION - Izza, Nadia Nurul; Rusydiana, Aam Slamet (The Pontianak State Institute of Islamic Studies, 2024)
This study tries to examine research on Islamic business education in Scopus indexed journals. The purpose of this research is to find out the map of research development related to Islamic Business in the field of education by using bibliometric mapping. The things described in the mapping are related to authors, institutions, countries, and keywords related to Islamic Business Education. This analysis uses descriptive statistical analysis of 153 selected papers related to Islamic business education. All samples of published journals have been published for 36 years from 1985 to 2021. The data is exported and then processed and analyzed using the VOSviewer application program to find out the bibliometric visualization map of Islamic business education research development results of the study show a map of the development of research in the field of Islamic business education. This research finds the link between Islamic business education and the SDGs goals manifested in the form of integrating knowledge, skills, and ethics to ensure the quality of education that is inclusive and sustainable and able to answer existing global problems.